Still life : the myths and magic of mindful living - Pacheco, Rebecca (Harper Wave, an imprint of HarperCollinsPublishers, 2021)
Deconstructing the common misperceptions about meditation and offering valuable insight into what mindfulness does entail, the creator of the popular yoga blog OmGal.com challenges readers to dig deep and develop the tools that can ultimately lead to joy.